Psychological contract breach among allied health professionals: Fairness, individual differences and an aggravated breach effect. Issue 3 (18th May 2015) - Rodwell, John; Gulyas, Andre
Abstract : Purpose: – Allied health professionals are vital for effective healthcare yet there are continuing shortages of these employees. Building on work with other healthcare professionals, the purpose of this paper is to investigate the influence of psychological contract (PC) breach and types of organisational justice on variables important to retention among allied health professionals: mental health and organisational commitment. The potential effects of justice on the negative outcomes of breach were examined. Design/methodology/approach: – Multiple regressions analysed data from 113 allied health professionals working in a medium-large Australian healthcare organisation. Findings: – The main negative impacts on respondents' mental health and commitment were from high PC breach, low procedural and distributive justice and less respectful treatment from organisational representatives. The interaction between procedural justice and breach illustrates that breach may be forgivable if processes are fair. Surprisingly, a betrayal or "aggravated breach effect" may occur after a breach when interpersonal justice is high. Further, negative affectivity was negatively related to respondents' mental health (affective outcomes) but not commitment (work-related attitude). Practical implications: – Healthcare organisations should ensure the fairness of decisions and avoid breaking promises within their control. If promises cannot reasonably be kept, transparency of processes behind the breach may allow allied health professionals to understand that the organisation did not purposefully fail to fulfil expectations. Originality/value: – This study offers insights into how breach and four types of justice interact to influence employee mental health and work attitudes among allied health professionals.